Green and facile preparation and dual-enhancement cytotoxicity of eupatilin loaded on hollow gold nanoparticles under near-infrared light. (10th August 2021) - Sun, Yi-wei; Liang, Hui; Zong, Kun-qi; Che, Xin; Meng, Da-li
Abstract : Using NIR irradiation, gold nanomaterials loaded with natural products can achieve targeted release as well as better anti-tumor activity. Abstract : Eupatilin, a strong biological activity compound, was isolated from Artemisia argyi and loaded onto hollow gold nanoparticles (E-HGNPs) for combined photothermal therapy and chemotherapy. In the cellular uptake assay under confocal laser scanning microscope observation, E-HGNPs can effectively pass through the cytomembrane and mainly locate around the nucleus through cell localization staining. The cell experiments indicated that the toxicity of HGNPs is negligible; E-HGNPs had a weak chemotherapeutic efficacy without NIR laser irradiation but showed excellent cytotoxicity under NIR laser irradiation due to the synergy of chemo-photothermal therapy. Based on the localized surface plasmon resonance (LSPR) properties, NIR laser illumination would drive the photothermal effect to release free eupatilin, inducing a more efficient photothermal conversion and stronger tumor-cell killing ability. In short, a NIR-triggered and LSPR-responded gold nanoparticle is a promising targeted drug delivery system for combined photothermal therapy and chemotherapy, which is worthy of application in other natural products.